Cambridge English IELTS 6 with answers : (Cambridge University press, 2017)
Provides students with an excellent opportunity to familiarise themselves with IELTS and to practise examination techniques using authentic test material prepared by Cambridge ESOL. Each collection contains four complete tests for Academic candidates, plus extra Reading and Writing modules for General Training candidates. An introduction to these different modules is included in each book, together with an explanation of the scoring system used by Cambridge ESOL. A comprehensive section of answers and tapescripts makes the material ideal for self-study.